Diagnosis and Management of Supernumerary (Mesiodens): A Review of the Literature - A. Pakdaman; G. Meighani (Tehran University of Medical Sciences, 2010)
Supernumerary tooth is one of the developmental problems in children. Mesiodens is a supernumerary tooth present in the midline between the two central incisors. It usually results in oral problems such as malocclusion, food impaction, poor aesthetics, and cyst formation. The prevalence of mesiodens varies between 0.09% and 2.05% in different studies. This paper reviews current literature on etiology, prevalence, diagnosis, and management of this problem. Accordingly, early diagnosis and treatment is suggested to prevent orthodontic and pathologic complications.